Anticipated verbal feedback induces altruistic behavior - Tore Ellingsen; Magnus Johannesson (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
A distinctive feature of humans compared to other species is the high rate of cooperation with non-kin. One explanation is that humans are motivated by concerns for social esteem. In this paper we experimentally investigate the impact of anticipated verbal feedback on altruistic behavior. We study pairwise interactions in which one subject, the divider, decides how to split a sum of money between herself and a recipient. Thereafter, the recipient can send an unrestricted anonymous message to the divider. The subjects' relationship is anonymous and one-shot to rule out any reputation effects. Compared to a control treatment without feedback messages, donations increase substantially when recipients can communicate. With verbal feedback, the fraction of zero donations decreases from about 40% to about 20%, and there is a corresponding increase in the fraction of equal splits from about 30% to about 50%. Recipients who receive no money almost always express disapproval of the divider, sometimes strongly and in foul language. Following an equal split, almost all recipients praise the divider. The results suggest that anticipated verbal rewards and punishments play a role in promoting altruistic behavior among humans.
Keywords: C91; D64; 330; Punishment; Approval; Disapproval; Dictator game; Altruism; Communication; Verbal feedback; Spieltheorie; Verhaltensökonomik; Soziales Verhalten; Altruismus